AKSELERASI MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR MELALUI PEMANFAATAN MEDIA MANIPULATIF BLOCK DIENES - Veronica Yonita Wongkar; Stief Aristo Walewangko; Agustina Regina Banua; Ignatius Rolly Cun Rorah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The primary issue examined in this study concentrates on the inadequate levels of motivation and defective learning outcomes in mathematics, particularly with regard to place value, among third-grade students at SD Negeri 72 Manado. The acceleration of student motivation and learning outcomes was achieved through modifications to instructional practices, including the use of block dienes media, and the implementation of specific and practical classroom management strategies. The subjects of this study were 24 third-grade students.The present study was conceived as a classroom-based action research project, which comprised two cycles of planning, action, observation, and reflection. The data presented herein were collected via a series of empirical methods, including tests, observations, interviews, documentation, and a learning motivation questionnaire. The findings of the study suggest that the utilisation of Dienes blocks as a medium for instruction can enhance students' motivation and academic performance in the domain of mathematics. With regard to the learning outcomes, the results of the students' pre-cycle tests demonstrated that a mere two out of 24 students met the proficiency standards, resulting in a proficiency rate of 8.33%. In Cycle I, the results of the assessments indicated that 8 out of 24 students demonstrated proficiency, with a proficiency rate of 33.33%. The number of students who met the proficiency criteria in Cycle II increased to 21 students, with a proficiency rate of 87%. Furthermore, an enhancement in students' learning motivation was also observed. In Cycle I, the mean score for learning motivation was 61.66%, with all motivation indicators falling within the